2014
DOI: 10.1111/ele.12352
|View full text |Cite
|
Sign up to set email alerts
|

Local‐scale biotic interactions embedded in macroscale climate drivers suggest Eltonian noise hypothesis distribution patterns for an invasive grass

Abstract: A hierarchical view of niche relations reconciles the scale-dependent effects of abiotic and biotic processes on species distribution patterns and underlies most current approaches to distribution modeling. A key prediction of this framework is that the effects of biotic interactions will be averaged out at macroscales - an idea termed the Eltonian noise hypothesis (ENH). We test this prediction by quantifying regional variation in local abiotic and biotic niche relations and assess the role of macroclimate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 53 publications
1
43
0
Order By: Relevance
“…Accordingly, this study is generally compatible with the conclusion that niche divergence is likely not the major driver of clade diversification process in Gynandropaa , while the three clades have seemingly originated through vicariance events27 associated with evolutionary conservatism in their environmental tolerances. It should be noted, however, that the niches fitted here were rather measured at the macro-environmental scale, and one cannot exclude from these results that niche differentiations may have occurred between clades at a more micro-environmental scale484950. In fact, both niche conservatism and niche divergence could be observed following a geographic separation depending on the geographic scale considered, which will also depend on the environment on all sides of the barriers.…”
Section: Discussionmentioning
confidence: 80%
“…Accordingly, this study is generally compatible with the conclusion that niche divergence is likely not the major driver of clade diversification process in Gynandropaa , while the three clades have seemingly originated through vicariance events27 associated with evolutionary conservatism in their environmental tolerances. It should be noted, however, that the niches fitted here were rather measured at the macro-environmental scale, and one cannot exclude from these results that niche differentiations may have occurred between clades at a more micro-environmental scale484950. In fact, both niche conservatism and niche divergence could be observed following a geographic separation depending on the geographic scale considered, which will also depend on the environment on all sides of the barriers.…”
Section: Discussionmentioning
confidence: 80%
“…Nevertheless, macroscale environmental conditions influence abiotic and biotic processes shaping species' niche spaces and distributions at local scales to different degrees (Fraterrigo et al ., , and references therein). Besides biotic interactions such as competition, numerous studies have shown that microclimate drives the spatial occurrence of species on small spatial scales (Maclean et al ., ; Opedal et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…There is a natural inclination to interpret SDMs as providing insights about the mechanisms shaping species' distributions (Alvarez‐Martínez, Suárez‐Seoane, Palacín, Sanz, & Alonso, ; Fraterrigo et al., ). Our results suggest that it is difficult to identify the effect of competition on species' distributions using SDMs under some circumstances, or to distinguish the effects of competition from other drivers.…”
Section: Discussionmentioning
confidence: 99%
“…Although SDMs are used to identify the importance of biotic interactions or other ecological mechanisms (Elith & Leathwick, ; Fraterrigo, Wagner, & Warren, ; le Roux, Lenoir, Pellissier, Wisz, & Luoto, ; Roux, Pellissier, Wisz, & Luoto, ; Sexton et al., ), there are sound statistical reasons to be skeptical of this approach. In particular, abiotic environment often indirectly influences the effects of biotic interactions (Callaway et al., ; Davis, Jenkinson, Lawton, Shorrocks, & Wood, ; Sexton et al., ; Tylianakis, Didham, Bascompte, & Wardle, ) and the resultant correlations among variables (i.e., multicollinearity) can make it difficult to infer how important each variable is for shaping species' distributions (Graham, ).…”
Section: Introductionmentioning
confidence: 99%